2017
DOI: 10.1111/hypa.12307
|View full text |Cite
|
Sign up to set email alerts
|

Collective Love as Public Freedom: Dancing Resistance. Ehrenreich, Arendt, Kristeva, andIdle No More

Abstract: In the Indigenous resistance movement that came to be known as “Idle No More,” round dances played a central role. From the beginning of the movement in western Canada in the winter of 2012–13, and as it spread across Turtle Island (North America) and throughout the world, round dances served to bring together Indigenous and non‐Indigenous activists with people in the streets. “At almost every event, we collectively embodied our diverse and ancient traditions in the round dance by taking the movement to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Dance, for its performative nature, is a "seductive way of embodying national or regional identities" (Neveu Kringelbach 2013, 10). Many dance studies have revealed that, when dance concerns one's or others' identities, it is a particularly salient vehicle to politically demonstrate such identities (Neveu Kringelbach and Skinner 2012;Royce 2002;Wulff 2008;Weir 2017;Spanos 2019). North American native communities, for instance, revive the traditional dance rituals to mark their distinct identities (Aplin 2009;Kelley 2012) or to protest for political rights (Harkin 1997;Weir 2017).…”
Section: Cultural Renaissance and The New Generation Of Kahiko Dancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Dance, for its performative nature, is a "seductive way of embodying national or regional identities" (Neveu Kringelbach 2013, 10). Many dance studies have revealed that, when dance concerns one's or others' identities, it is a particularly salient vehicle to politically demonstrate such identities (Neveu Kringelbach and Skinner 2012;Royce 2002;Wulff 2008;Weir 2017;Spanos 2019). North American native communities, for instance, revive the traditional dance rituals to mark their distinct identities (Aplin 2009;Kelley 2012) or to protest for political rights (Harkin 1997;Weir 2017).…”
Section: Cultural Renaissance and The New Generation Of Kahiko Dancersmentioning
confidence: 99%
“…Many dance studies have revealed that, when dance concerns one's or others' identities, it is a particularly salient vehicle to politically demonstrate such identities (Neveu Kringelbach and Skinner 2012;Royce 2002;Wulff 2008;Weir 2017;Spanos 2019). North American native communities, for instance, revive the traditional dance rituals to mark their distinct identities (Aplin 2009;Kelley 2012) or to protest for political rights (Harkin 1997;Weir 2017). Hula, especially its precolonial variant, has often been employed as a symbol to demonstrate Hawaiian Indigenous identity and sovereignty since the 1970s.…”
Section: Cultural Renaissance and The New Generation Of Kahiko Dancersmentioning
confidence: 99%
“…To find philia among these challenging others may require acknowledgment of the other within ourselves. We can form common cause through hopeful and loving examples, from expressions of cathartic communal dance led throughout Canada by Indigenous activists (Weir, 2017) to interfaith movements to protect Muslims from harassment as they pray. We learn from the Indigenous planning scholars cited at the beginning of the provocation that many struggles in planning ought to be led by communities that have their own ways of knowing, being, and doing.…”
Section: Part 2: Commentaries and Responsesmentioning
confidence: 99%
“…Tıpkı kendi çalışma ve düşün dünyasında olduğu gibi pek çok çalışmanın da disiplinler üstü/arası bir alanda benzer eğilim ve içerikte üretildiği görülmektedir. Psiko-analitik düşünceyi kadın hakları ve toplumsal cinsiyet yönüyle birey, bireysellik ve kimlik odağında ele alan(Elliott, 2012), maternale ve doğum/doğarlık ilişkisine Arendt ile paslaşarak yaklaşan siyaset bilimi, felsefe ve feminist örüntüyle irdeleyen(Birmingham, 2003), Kristeva'nın psiko-analitik bağlamını Avrupa, kozmopolitanizm ve ötekilik kavramlarıyla yoğuran(Varsamopoulou, 2009), kamusallık, yerli halk mücadelesi, aktivizm eylemliklerinden hareketle kamusal hak ve talepleri sorgulayan(Weir, 2017), homoseksüellik ve homofobik yaklaşıma değinen(Gambaudo, 2013), meşhur "abject" (iğrenç, tiksinç) kavramı odağında beden-toplumsal cinsiyet ve edebiyatı birlikte kritik eden(Çolak, 2011), sanat, beden ve psiko-analitik bir bağlamda sorgulama yapan(Şener, 2014), felsefi arayışını choraya odaklanarak irdeleyen(Kymalainen & Lehtinen, 2010;Randhawa, 2014;Rickert, 2007) çalışmalardan yukarıda ifade edilen çoklu çalışma ve yaklaşım üreten metin örnekleri olarak bahsedilebilir.…”
unclassified